An Efficient and Reliable Procedure for the Preparation of Highly Reactive Rieke Zinc. Issue 2 (25th January 2013) - Kudret, Suleyman; Haen, Jan D'; Lutsen, Laurence; Vanderzande, Dirk; Maes, Wouter
Abstract Rieke zinc has a wide potential for applications in organic chemistry, notably for the synthesis of highly chemoselective organozinc reagents. However, due to the rather unreliable preparation method, leading to large batch to batch variations, its use has been rather limited. Rieke zinc is commonly prepared by the reduction of zinc chloride with lithium using a stoichiometric amount of naphthalene. In our hands, it was observed that the reaction outcome was highly dependent on the naphthalene source and purity grade. The presence of benzothiophene seems crucial to avoid coagulation of the zinc particles and the amount of benzothiophene has a large effect on the physical properties and the reactivity of the resulting zinc powder. Accordingly, highly reactive Rieke zinc was easily prepared from zinc chloride by adding an optimum amount (3 mol% with regard to ZnCl2) of benzothiophene into the lithium naphthalenide solution (prepared in situ). The Rieke zinc obtained in this way was successfully employed in the so‐called "Rieke method" to prepare regioregular poly(3‐hexylthiophene) (P3HT). The novel approach enables preparation of Rieke zinc in a reproducible manner, which considerably facilitates its use in both small molecule and polymer synthesis.